The Contribution of School’s Characters to the Effectiveness of Entrepreneurial Learning Based on Local Wisdom - Endah Andayani; Lilik Srihariani; Suko Winarsih; Rusno Rusno (International Journal of Pedagogy and Teacher Education, 2017)
Entrepreneurial learning in SMK Negeri 2 Turen Malang quite effective. The learning process is used in addition to learning theory in the classroom also apply the learning in the real world based on the values of local wisdom and economic potentials that exist around the school, so that students are able to have sufficient ability to forward, assess and put this potential in a strategic position to be developed towards the management of natural resources and towards a better environment. To achieve the ultimate goal of effective entrepreneurial learning, the necessary supporting character. This type of research is descriptive research for photographing like what the character of the students in entrepreneurial learning, with a sample of 52 students in class X and XI in SMK Negeri 2 Turen. The results showed that the students are very happy to work hard by 48%; risk-taking 69.3%; think carefully before taking the plunge 55.8%; think far ahead 57.7%; high spirit for entrepreneurship 67.3%; apply the principle of saving 51.9%; 75% had a constructive spirit; strong-willed to create jobs for themselves, 71.2%; 34.6% have a creative spirit; the desire to live independently 73%; appreciate the time, 61.5%; perform the act of earning more dominant than on the actions of the consumer, 30.8%; confident 48.1%; discipline, 76.9%; diligently 57.7%; difficult to take the initiative in making a work of 34.6%; reluctant to obtain enormous responsibility of 63.4%; happy if it can do the work efficiently 75%; quickly bored 55.8%; and meticulous task of 46.2%. Except where otherwise noted, content on this site is licensed under a Creative Commons Attribution 4.0 International License.